Variations in Length and Weight of Oreochromis mossambicus in Malir River, Karachi, Pakistan - Bano, Farida; Rizvi, Syeda Nazneen; Farooq, Sumera (Journal of Basic & Applied Sciences, 2012)
Aquatic pollution results in physical, chemical and biological deterioration of water bodies causing destruction of fish and other biota. Fishes are now considered as the best indicators of pollution. The present study was conducted to see the extent of pollution in Malir River by studying the growth of Oreochromis mossambicus, the common fish of this river. During the study, analysis of length and weight has been done primarily to describe their relationship and to measure the variations in growth of an individual or population. The data showed that the growth was higher at spot 3 (Drigh road) and lower at spot 4 (Quyumabad). It appeared that the good water condition at Spot 3 was supporting the higher fish growth at this spot whereas the polluted water at Spot 4 results in the poor growth of the fish.